Investigating Cognitive-Based Storytelling Technique (CBST) of Learning Narrative Reading - Halimatul Aulia (INGGARA (Jurnal Pendidikan Bahasa Inggris dan Bahasa Arab), 2023)
Reading is a multifaceted process that involves word recognition, comprehension, fluency, and motivation. To develop this competence, a creative technique is intended to be applied. This study aims to investigate the effectiveness of the Cognitive-Based Storytelling Technique (CBST) in learning narrative texts. Both descriptive and inferential statistics were employed in this research. The primary assessment tool used was a test. The participants in this study consisted of 263 second-year students from MAN Selong, all of whom were deemed to have similar characteristics. The data obtained for the experimental group in the pre-test ranged from a minimum score of 3 to a maximum score of 14. In the post-test, the lowest score observed was 8, while the highest was 14. For the control group, the pre-test results ranged from a minimum of 3 to a maximum of 13. In the post-test, the lowest and highest scores were 4 and 14, respectively. Subsequently, the calculated mean scores for the experimental group in the pre-test and post-test were 8.08 and 11.11, respectively. For the control group, the mean scores in the pre-test and post-test were 7.36 and 7.91. These results will be further discussed in the subsequent sections.